Level of transparency at public budget hearings in large municipalities - Mesquita, Tiemi Suzuki; Azevedo, Ricardo Rocha de (Advances in Scientific and Applied Accounting, 2024)
Objective: The research examines the literature on budget transparency, seeking to analyze the level of transparency of information about public budget hearings on municipal governments’ online portals. Method: Information about budget hearings was collected on the transparency portals of large municipal governments. Information on the annual budgetary law, budgetary guideline law, and monitoring of fiscal targets was analyzed quantitatively through mean difference tests and descriptive analyses. Results: The results indicate a low level of transparency of information about public hearings in large municipalities, which suggests that the hearings should be held ceremonially. The research shows that the level of informatization of municipalities and the fact that they are capitals do not affect transparency. This allows us to infer that differences may be motivated by other factors, such as political will and external pressures. Contributions: Transparency of the information presented at public budget hearings, and not just disclosure during the event, can provide greater participation and trust in the process, making the information visible to citizens. The research contributes to the transparency literature for instrumentalizing participation by focusing on the transparency of the process for citizens. The results suggest practical implications for citizens and information users, for public managers regarding improving the transparency of the process, and for control bodies, which could exert greater pressure through their oversight.